FUN WAYS SEBAGAI STRATEGI MEMOTIVASI SISWA BELAJAR BAHASA INGGRIS PADA SDN 250 SAPARUA TIMUR - Nikijuluw, Maria Martha (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
The problem faced by most elementary schools in Maluku, including SDN 250, East Saparua District, Central Maluku Regency, is that they do not receive English lessons at school. However, learning English from a young age is crucial in the current era of globalization. Therefore, community service activities (PkM) carried out through the teaching assistance program also provide English language teaching assistance at the school. This community service activity took place in December 2022 and is directed as "fun" learning English using the English songs via YouTube videos. The results of this PkM prove that implementing fun learning can motivate students to learn English and master vocabularies, with the results of writing English words very well (correctly), as evidenced by a total of 23 students (working in pairs, 16 students or 8 sheets) who were able to write words correctly (more than 70%), which means that the "fun" method can motivate students to learn English and can train students' ability to understand English words well too